DETERMINANT FACTORS OF UNCONTROLLED HYPERTENSION AMONG ADULT - Helmi Rumbo (Berkala Kedokteran, 2022)
Abstract: Uncontrolled high blood pressure can lead to stroke, heart attack, kidney failure, memory and vision disfunction, and also erectile dysfunction. Globally, data shows that 1.28 billon adults aged 30 – 79 years has hypertension and estimated only 46% of adults with hypertension are diagnosed and treated. In Indonesia, based on national survey in 2019, an estimated 34.11% of the population aged 18 years above has hypertension. Division of Disease Control and Environmental health in Central Sulawesi Province proofed that only 0.12 % of hypertensive patients have been recorded to get treatment or visited to the health Center in Parigi Moutong District. This study aims to identify the determinant factors of uncontrolled hypertension among hypertensive patients in Taniuge, Parigi Moutong District. Community- based cross sectional study design was conducted 25 July to 6 August 2021. Total sampling method was used to select 30 sample. Data was collected using the structured questionnaire. Chi-square test was used to identify the relationship between the variables. The results show that, there is relationship between life style and uncontrolled hypertension (p = 0.029); there were no relationship between genetic, family support and health center availability and uncontrolled hypertension (p = 0.6; p = 1.0; p = 0.5, sequentially). The conclusion is to control blood pressure, patients are recommended to take medication regularly, and also apply the Healthy Living Community Movement (GERMAS). All people are encouraged to adopt a healthy lifestyle, such as not smoking, consuming balanced nutrition, daily physical activity for at least 30 minutes; in order to reduce risk factors for hypertension.Keywords: Hypertension; Uncontrolled; Adult; Life-style